Primer caso de nidificación de un geotrupino (Scarabaeoidea: Geotrupidae) en cuevas: un fenómeno excepcional - Halffter, Gonzalo; Deloya, Cuauhtémoc (Instituto de Ecología, A.C., 2007)
The Tasalolpan cave in the state of Puebla, Mexico is the only cave in the world where three species of Scarabaeoidea are found together: a geotrupine, a scarabaeine and an aphodine. As shown in this communication, the first two species appear to be troglobites: they have never been collected outside of the cave in spite of intensive searches, and it has been confirmed that at least one of them (the geotrupine) nests in the cave.